Breast cancer mastectomy trends between 2006 and 2010: association with magnetic resonance imaging, immediate breast reconstruction, and hospital volume - Heil, Jörg; Rauch, Geraldine; Szabo, Akos; Golatta, Michael; Domschke, Christoph; Schütz, Florian; Wallwiener, Markus; Sohn, Christof; Schneeweiss, Andreas (Annals of surgical oncology, 2013)
Analysis of mastectomy rates in breast cancer patients diagnosed between 2006 and 2010 in Germany with focus on impact of breast magnetic resonance imaging (MRI), immediate breast reconstruction (IBR) rates, and hospital volume as possible influencing factors of mastectomy rates.
Gesehen am 08.10.2021